Validating dilute settling suspensions numerical data through MRI, UVP and EIT measurements. (August 2016) - Silva, R.; Garcia, F.A.P.; Faia, P.M.; Krochak, Paul; Söderberg, Daniel; Lundell, Fredrik; Rasteiro, M.G.
Abstract: The measurement of fluid dynamic quantities are of great interest both for extending the range of validity of current correlations to be used in equipment design and for verification of fundamental hydrodynamic models. Studies where comparisons are made between imaging techniques serve to provide confidence on the validity of each technique for the study of multiphase flow systems. The advantage of cross-validation is that it can help establish the limitations of each technique and the necessary steps towards improvement. A small amount of comparative studies are found in the literature and none of them reports the study of settling particles suspension flow using simultaneously Ultrasonic Velocity Profiling (UVP), Magnetic Resonance Imaging (MRI) and Electrical Impedance Tomography (EIT), at least not to the best of the authors knowledge. In the present paper the authors report efforts made on the characterization of dilute suspensions of glass particles in turbulent flow, with increasing flow velocities and particles concentrations, in a pilot rig at a laboratorial scale, using both MRI, EIT and UVP: direct comparisons of EIT, MRI and UVP measurements acquired and mixture model numerical simulations are presented and the level of agreement explored. Graphical abstract: Highlights: MRI, UVP and EIT techniques are used to characterize dilute solid-liquid flows. Data is compared between experimental velocity profiles in solid-liquid flows. The effect of particle size and concentration on the flow is demonstrated. Validation of the mixture model numerical results with the experimental data.